2023
DOI: 10.1093/plphys/kiad292
|View full text |Cite
|
Sign up to set email alerts
|

PmAGAMOUS recruits polycomb protein PmLHP1 to regulate single-pistil morphogenesis in Japanese apricot

Abstract: Japanese apricot (Prunus mume Sieb. et Zucc.) is a traditional fruit tree with a long history. Multiple pistils (MP) lead to the formation of multiple fruits, decreasing fruit quality and yield. In this study, the morphology of flowers was observed at four stages of pistil development: undifferentiated stage (S1), pre-differentiation stage (S2), differentiation stage (S3), and late differentiation stage (S4). In S2 and S3, the expression of PmWUSCHEL (PmWUS) in the MP cultivar was significantly higher than tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…Based on their proximity to AtKNAT2 and AtKNAT6 in the phylogenetic tree, these genes were named PmKNAT2/6-a and PmKNAT2/6-b, respectively; since overexpression of KNAT2 in Arabidopsis expands AGAMOUS ( AG ) expression in carpels and ovules and forms ectopic carpel structures ( Ragni et al 2008 ). And in our previous study, we demonstrated that AG may be involved in the formation of Japanese apricot multi-pistil, so the gene function of PmKNAT2 in P. mume is well worth studying in depth ( Shi et al 2023 ). To further analyze the role of PmKNAT2/6-a and PmKNAT2/6-b in pistil number determination in Japanese apricot, reverse transcription quantitative PCR (RT-qPCR) experiments were conducted on flower buds from the pistil differentiation stage of 2 pistil varieties, ‘Longyan’ (‘LY’, single-pistil variety) and ‘Dayu’ (‘DY’, multi-pistil variety) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Based on their proximity to AtKNAT2 and AtKNAT6 in the phylogenetic tree, these genes were named PmKNAT2/6-a and PmKNAT2/6-b, respectively; since overexpression of KNAT2 in Arabidopsis expands AGAMOUS ( AG ) expression in carpels and ovules and forms ectopic carpel structures ( Ragni et al 2008 ). And in our previous study, we demonstrated that AG may be involved in the formation of Japanese apricot multi-pistil, so the gene function of PmKNAT2 in P. mume is well worth studying in depth ( Shi et al 2023 ). To further analyze the role of PmKNAT2/6-a and PmKNAT2/6-b in pistil number determination in Japanese apricot, reverse transcription quantitative PCR (RT-qPCR) experiments were conducted on flower buds from the pistil differentiation stage of 2 pistil varieties, ‘Longyan’ (‘LY’, single-pistil variety) and ‘Dayu’ (‘DY’, multi-pistil variety) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, we identified the epigenetic factor PmLHP1 with the function of recognizing and recruiting H3K27me3 and its important role in the pistil number differentiation process in Japanese apricot ( Shi et al 2023 ). Since the Class I KNOTTED1-like homeobox ( KNOX ) genes in Arabidopsis were enriched in tri-methylated lysine 27 of histone H3 (H3K27me3) modifications ( Zhang et al 2007 ), we hypothesized that histone methylation is involved in the PmKNAT2/6-a-mediated multi-pistil construction process.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations